2008
DOI: 10.1021/ie8001815
|View full text |Cite
|
Sign up to set email alerts
|

Emulsion Texture and Stability: Role of Surfactant Micellar Interactions in the Presence of Proteins

Abstract: This article presents the results of our recent research on the texture and stability of oil-in-water emulsions containing sucrose ester and proteins. We used both the direct microscopic imaging and nondestructive back-light scattering (Kossel diffraction) techniques to evaluate the emulsion texture and the energy barrier between droplets for two different emulsifier compositions with and without the proteins present. The microinterferometric method employing our capillary force balance was used to study the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The milk ring formation, or "oiling off", is accelerated in these drinks. Moreover, the average drop size distribution of the combined emulsifier system containing protein (in this case, milk proteins) increases because the protein induces an attractive depletion interaction between droplets, thereby inducing flocculation and coalescence [37]. This situation is aggravated by the fact that the plastic bottle is transparent: consumers can see that the milk fat has separated, so the product value depreciates.…”
Section: Milk-coffee and Rich-milk-coffee Beveragesmentioning
confidence: 99%
“…The milk ring formation, or "oiling off", is accelerated in these drinks. Moreover, the average drop size distribution of the combined emulsifier system containing protein (in this case, milk proteins) increases because the protein induces an attractive depletion interaction between droplets, thereby inducing flocculation and coalescence [37]. This situation is aggravated by the fact that the plastic bottle is transparent: consumers can see that the milk fat has separated, so the product value depreciates.…”
Section: Milk-coffee and Rich-milk-coffee Beveragesmentioning
confidence: 99%
“…However, high sensitivity to temperature, pH, and ionic strength of protein stabilized emulsions have offered a constraint to their use in many food products . Kong et al studied the stability of emulsions prepared by protein and sucrose ester and discussed the micellar interaction in emulsion containing protein. Dunlap and Côté found that increasing the size of the polysaccharide conjugated with β-lactoglobulin resulted in more stable emulsions.…”
Section: Introductionmentioning
confidence: 99%
“…This long-range structure results in a repulsive structural barrier that prevents the droplets from approaching each other. In general, the effective pair interaction potential induced by surfactant micelles or nanocolloids layering between two droplets in the presence of other droplets is oscillatory, including both the attractive depletion (i.e., so that no micelles can fit in the gap between the droplets) and the repulsive structural barrier. Our theoretical calculations based on the statistical mechanics approach have clearly indicated that the structural energy barrier is large enough to prevent the droplets from approaching each other when the effective micelle concentration (including the double layer and hydration layer) is 20 vol % or higher. , …”
Section: Introductionmentioning
confidence: 85%
“…In general, the effective pair interaction potential induced by surfactant micelles or nanocolloids layering between two droplets in the presence of other droplets is oscillatory, including both the attractive depletion (i.e., so that no micelles can fit in the gap between the droplets) and the repulsive structural barrier. [1][2][3][4][5][6][7][8][9][10][11] Our theoretical calculations based on the statistical mechanics approach have clearly indicated that the structural energy barrier is large enough to prevent the droplets from approaching each other when the effective micelle concentration (including the double layer and hydration layer) is 20 vol % or higher. 12,13 Emulsion stability based on the number of drops and their size distribution over time is defined in different ways: flocculation, coalescence, and Ostwald ripening.…”
Section: Introductionmentioning
confidence: 92%